THE OUTPATIENT BASED REGISTRY RECVASA: PROSPECTIVE FOLLOW-UP DATA, RISK EVLUATION AND OUTCOMES IN CARDIOVASCULAR PATIENTS - S. A. Boytsov; М. М. Lukyanov; S. S. Yakushin; S. Yu. Martsevich; A. N. Vorobyev; A. V. Zagrebelny; K. G. Pereverzeva; Е. А. Pravkina; A. D. Deev; E. Yu. Andreenko; A. I. Ershova; A. N. Meshkov; et al. (Кардиоваскулярная терапия и профилактика, 2015)
Aim. To evaluate, under the frame of prospective registry, the 12-month outcomes and risks in patients with arterial hypertension (AH), ischemic heart disease (CHD), chronic heart failure (CHF) and atrial fibrillation (AF) in the real outpatient practice in Ryazan Region. Material and methods. Into the outpatient registry RECVASA (REgistry of CardioVAScular diseases) totally 3690 patients included with AH, CHD, CHF, AF and their comorbidity, visited 3 outpatient institutions in Ryzan city: 1047 (28%) of men and 2643 women, mean age 66,1±12,9 y.o. The estimation of 12-mint risk of events fter inclusion in registry RECVASA was done for 3619 (98,1%) participants. Results. By 12 month after inclusion 168 patients (4,6%) died, had stroke (S) — 62 (1,7%), myocardial infarction (MI) — 26 (0,7%), cardiovascular surgery (CVS) — 6 (0,2%). Totally 235 hospitalizations for CVD registered. The risk of death, MI development and S had been increasing by 5-9% every year of patient age, and CVD hospitalization — decreased by 2%. Combined death risk and cardiovascular death risk were significantly higher (1,3-6,4 times) with anamnesis of MI, S, diabetes mellitus (DM), chronic obstructive lung disease (COPD), CHF of 3-4 functional class (FC), in males and with blood pressure (BP) <110/75 mmHg, heart rate (HR) >90 bpm, glomerular filtration rate (GFR) <45 ml/min. Higher MI risk (1,8-3,4 times) was linked to the anamnesis of diabetes and MI, angina pectoris (FC 3-4) and GFR <45 ml/min. MI risk was higher by 2,4-7,2 times in patients with anamnesis of MI, permanent AF, and with combinations of AH, CHD, CHF and AF, with BP <110/75 mmHg and >180/110 mmHg, HR >90/min. Risk of all-cause death was lower in those who received p-adrenoblockers, angiotensin-converting enzyme inhibitors (iACE) and angiotensin receptor blockers (ARB) 1,4-1,5 times, death from cardiovascular causes — with iACE and ARB — 2 times lower. Patients on p-blockers had 1,8 times lower risk of MI. Conclusion. Prospective follow-up of cardiovascular patients under the frame of RECVASA registry showed significant negative influence on prognosis the following: age, male gender, anamnesis of MI and S, DM, COPD, CHF (3-4 FC), angina (3-4 FC), permanent AF, BP <110/75 and >180/110 mmHg, GFR <45 ml/min, HR >90/min, combination of AH, CHD, CHF and AH, CHD, CHF, AF. Positive influence on prognosis with CVD had treatment with p-adrenoblockers, iACE, ARB.